Adaptive Mechanisms During the Recovery of Tolerant and Sensitive Local Grape Genotypes Subjected to Salt Stress - Mahmoud, Rania; Ashry, Fouad; Shallan, Roqaya (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Utilization of distinct genetic resources is an auspicious prospective strategy to combat adverse impacts of salinity, which is expected to get worse under climate change conditions, for maintaining grape production and quality. This research aims to study the adaptive mechanisms during the recovery of tolerant and sensitive salt-stressed local grape genotypes on the bases of biochemical, anatomical and gene expression responses. Transplants of three Egyptian grapes (Vitis vinifera); Baltim Eswid, Romy Ahmer and Romy Abiad, were exposed to sodium chloride-induced salt stress of 2.28 and 3.75 mS compared to 695 µS water-irrigated control for two months, then all plants were irrigated with tap water for additional one month for recovery. Recovered Baltim Eswid cultivar following the highest saline treatment gave maximum survival percentage (100 %), while Romy Abiad recorded the lowest rate (40 %). Suggested adaptive mechanisms include: damage reduction caused by salinity-related oxidative stress, osmotic adjustment, and perform structural modifications that allow protection. It was concluded that, Blatim Eswid is a superior salt-tolerant local grape genotype, while Romy Abiad is the most sensitive as affected mostly by oxidative stress represented by a significant increment of hydrogen peroxide content.